2022
DOI: 10.3389/fmed.2022.966632
|View full text |Cite
|
Sign up to set email alerts
|

Potential limitations in systematic review studies assessing the effect of the main intervention for treatment/therapy of COVID-19 patients: An overview

Abstract: BackgroundAlthough several studies have assessed the safety, efficacy, and effectiveness of interventions in treating the COVID-19, many of them have limitations that can have an immense impact on their results. This study aims to assess the potential limitations in systematic reviews (SRs) that evaluate the effect of interventions on the treatment of the COVID-19.MethodsPubMed, Scopus, and Web of Sciences (WOS) databases were searched from inception to January 1, 2022. All systematic reviews investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Typically, the two most common types of reviews carried out in academic research are systematic and bibliometric, both of which have advantages and disadvantages [18]. Systematic reviews allow for a deep analysis of research identifying what is already known but importantly, identifying potential gaps in research which can allow researchers to then explore those areas further [19]. When conducting the initial search of data, however, if too many search results are yielded, this can often make the systematic review method more difficult from a time perspective and, as such, a bibliometric analysis may offer a better alternative [18].…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the two most common types of reviews carried out in academic research are systematic and bibliometric, both of which have advantages and disadvantages [18]. Systematic reviews allow for a deep analysis of research identifying what is already known but importantly, identifying potential gaps in research which can allow researchers to then explore those areas further [19]. When conducting the initial search of data, however, if too many search results are yielded, this can often make the systematic review method more difficult from a time perspective and, as such, a bibliometric analysis may offer a better alternative [18].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, based on the literature, we followed several methods to assess the quality of our systematic literature review and the studies included; that is, we used some common methods: in addition to the PRISMA checklist, the methodological quality of the reviews included was assessed using the AMSTAR2 (A Measurement Tool to Assess Systematic Reviews) quality assessment tool, which showed moderate quality of the studies included. Moreover, we used NHLBI Study Quality Assessment Tools in order to assess the quality of the studies included [15][16][17]. This SR was registered in PROSPERO (no.…”
Section: Methodsmentioning
confidence: 99%
“…We have selected RCTs for this systematic review. The systematic review has its inherent trouble, such as hazards of bias, such as selection bias, insufficient blinding, abrasion bias, and selective outcome reportage; a discrepancy that comprises clinical or statistical heterogeneousness; and inaccuracy that can lead to Type I and Type II errors [ 151 ].…”
Section: Reviewmentioning
confidence: 99%